IDENTIFIKASI SISTEM PENGANGKUTAN SAMPAH KOTA BANJARMASIN - Akbar, Muhammad; Mizwar, Andy; Hidayat, Achmad Syamsu; Mahyudin, Rizqi Puteri (EnviroScienteae, 2024)
The number and distribution of TPS in the City of Banjarmasin currently does not meet the waste service needs of the City of Banjarmasin. The unequal distribution of TPS facilities has caused rubbish to pile up at several TPSs due to the lack of number of TPSs and the lack of TPS services. The step needed to overcome this problem is to identify the existing condition of the Banjarmasin City waste transportation system. Data collection was carried out by observation and interviews, then the data was processed by descriptive analysis. The research results show that the existing condition of the Banjarmasin City waste transportation system currently has 70 waste transport fleets which are divided into 3 types, namely 27 units of armroll trucks, 33 units of dump trucks, and 10 units of compactor trucks. The waste transportation pattern in Banjarmasin City uses the HCS transportation pattern for the Armroll truck fleet and the SCS transportation pattern for the dump truck and compactor truck fleet.